Loss of vacuolar-type H+-ATPase induces caspase-independent necrosis-like death of hair cells in zebrafish neuromasts - Peu Santra; Jeffrey D. Amack (The Company of Biologists, 2021)
The vacuolar-type H+-ATPase (V-ATPase) is a multi-subunit proton pump that regulates cellular pH. V-ATPase activity modulates several cellular processes, but cell-type-specific functions remain poorly understood. Patients with mutations in specific V-ATPase subunits can develop sensorineural deafness, but the underlying mechanisms are unclear. Here, we show that V-ATPase mutations disrupt the formation of zebrafish neuromasts, which serve as a model to investigate hearing loss. V-ATPase mutant neuromasts are small and contain pyknotic nuclei that denote dying cells. Molecular markers and live imaging show that loss of V-ATPase induces mechanosensory hair cells in neuromasts, but not neighboring support cells, to undergo caspase-independent necrosis-like cell death. This is the first demonstration that loss of V-ATPase can lead to necrosis-like cell death in a specific cell type in vivo. Mechanistically, loss of V-ATPase reduces mitochondrial membrane potential in hair cells. Modulating the mitochondrial permeability transition pore, which regulates mitochondrial membrane potential, improves hair cell survival. These results have implications for understanding the causes of sensorineural deafness, and more broadly, reveal functions for V-ATPase in promoting survival of a specific cell type in vivo.